A new approach to the integrated calibration in flow injection analysis - Koscielniak, P; Akcin, G; Herman, M; Kozak, J; Wieczorek, M (SOC CHIMICA ITALIANA, 2003)
A new proposal how to perform the analytical procedure according to the integrated calibration method is presented. An original flow injection system has been designed for this purpose. When using only a single standard solution, the measurement information gathered during a single analytical course permits construction of four calibration graphs and calculation of as many as four independent estimations of the analyte concentration in the sample examined. As the calibration method applied integrates the set of standards method and the standard addition method, the analytical estimations may be obtained in both the interpolative and the extrapolative manner and the final result can be effectively verified in terms of accuracy. The system developed was experimentally tested on the example of spectrophotometric determination of chromium. It has been proved to be capable of saving time and reagents as well as providing reliable analytical results. Owing to the instrumental simplicity and analytical efficiency the system is expected to be useful for routine analysis.
Keywords: ATOMIC-ABSORPTION-SPECTROMETRY; GRADIENT RATIO CALIBRATION; STANDARD ADDITION METHOD; SINGLE STANDARD; SYSTEM; VALVE; Chemistry; Environmental Sciences & Ecology